Pedoman Penyelenggaraan Peradilan Perdamaian Adat di Aceh - Nurdin MH Nurdin MH (Universitas Syiah Kuala, 2010)
ABSTRACT: Customary law of Aceh has a number of legal principles such as acceptable, accountability, non-discrimination/equality before the law; accessible to the public, win-win solution, consensus, transparency, competent, and presumption of innocence. The principles are not only found in Adat Law of Aceh but also in other civilized legal systems in the world. In practice, the principles are applied strictly (see the case of Sultan Iskandar Muda). Adat guidelines or legal procedure of Adat is badly needed by informal justice providers in order to have legal certainty. There are some reasons why the guide line is necessary; (1) during new order (35 years) central government denied the existence of adat law, (2) during the conflict era (30 years) Acehnese did not have enough opportunity to practice their customary law, and (3) most of you people today are head of village and they do not have enough knowledge and experience on guide line of adat. The Application Guideline of Informal Justice in Aceh